Literasi Kesehatan Mental di Institusi Kesehatan - Abdul Gani; Ira Kusumawaty; Yunike Yunike (Journal of Telenursing (JOTING), 2023)
This study aims to identify literacy in health institutions regarding mental health as a foundation for designing mental health literacy improvement programs. A survey was conducted with students and staff of college health education institutions to investigate the Understanding of depression, intentions to seek help, beliefs about interventions, and stigmatizing attitudes. Methods: This study used a cross-sectional and quantitative approach to determine the percentage of mental health literacy. The participants in this study were nursing students from several health institutions in Indonesia and involved staff from participating health institutions via telephone interviews. Participants answered research questions related to mental health literacy. The results showed that after the interviews were completed, 270 students (91%) and 24 staff (9%). More than 60% of students and staff can recognize depression, and most are female. Some 75% of respondents said they would seek help if they had a problem similar to the illustration for depression. However, the level of intention to seek special assistance for students is relatively low; only 20% choose a doctor, and only 2% seek the help of a counselor in dealing with mental health problems. Factors related to stigmatization include male gender, younger age, lower education level, and lack of Understanding of depression. In conclusion, there is a need for mental health literacy interventions aimed at college students, especially those who are younger, male, and with lower levels of education. A need fulfillment strategy is needed to help seek professional assistance, referring to the results of exploring the complexity of the obstacles experienced. Keywords: Health institutions, Mental health literacy, Understanding